Upaya Peningkatan Produktifitas UKM Kue Madumongso di Serengan Surakarta - Nugroho, Arif Setyo; Rahayu, Aris Teguh; Suhartoyo, Suhartoyo (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2025)
This community service program aims to improve the productivity of Madumongso Cake UKM owned by Mrs. Surti in Serengan, Surakarta, through the application of a motor-driven dough mixer. Previously, mixing was done manually, requiring long working time, significant physical effort, and yielding inconsistent dough quality. The team from STT Warga Surakarta designed a 5 kg-capacity mixer powered by a 0.5 HP electric motor with a pulley–belt transmission and low-pressure LPG heating pan. Testing on site compared time efficiency, dough quality, and production capacity before and after using the machine. Results show a 50% reduction in production time, a twofold increase in productivity, and smoother, more uniform dough. The machine also reduced operator fatigue and LPG fuel use. This simple technological innovation provides tangible economic, social, and educational benefits for the SME partner and strengthens collaboration between higher education and the community.